Effect of additive structure on the performance of biodiesel fuel winterization. (1st April 2021) - Abe, Masahiro; Nakamura, Ryosuke; Komatsu, Hiroyuki; Yamagiwa, Kazuaki; Tajima, Hideo
Highlights: Effects of additive structure on winterization results were examined systematically. Six sorbitan derivatives and seven palmitate derivatives were selected as additives. Additives with fatty-acid carbon chain lengths identical to FAME were most effective. Additive ester groups must have cyclic structures and OH groups. Span 40, which has palmitate and sorbitan groups, was the most effective additive. Abstract: The effects of additive structure on the separation of saturated fatty acid methyl esters (FAMEs) from FAME mixtures by winterization were investigated. Six sorbitan derivatives, seven palmitate derivatives, and sorbitan monopalmitate, which is known to improve the low-temperature separation of FAME mixtures, were studied. A model FAME mixture was prepared by blending saturated FAME (methyl palmitate) and unsaturated FAME (methyl oleate). Sorbitan derivatives that had fatty-acid groups with the same carbon chain length as the main saturated FAME in the FAME mixture improved the separation significantly. Shorter chain lengths and unsaturated fatty acid groups did not promote the winterization of FAME mixtures because their interactions with the main saturated FAME were too weak. Cyclic structures and hydroxy (OH) groups in the ester groups of the palmitate derivatives were found to be essential for preventing crystal growth and liquid contamination of the recovered solid phase. Cyclic structures affected the appearance of the FAME mixture during winterization, and the presence of OH groups affected the separation factor and the cloud point (CP) of the recovered liquid FAME. Span40, which has palmitate and sorbitan groups, was found to be the most effective additive for mixtures containing approximately 50 wt% methyl palmitate. The CP of the recovered liquid decreased 4–9 K, and the separation factors were between 3.6 and 7.5. These results will be useful for the separation and purification of saturated rich-FAME mixture such as palm, lard, mahua, neem, and jatropha biodiesels.